Optimal sticky prices under rational inattention - Bartosz Maćkowiak; Mirko Wiederholt (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
In the data, individual prices change frequently and by large amounts. In standard sticky price models, frequent and large price changes imply a fast response of the aggregate price level to nominal shocks. This paper presents a model in which price setting firms optimally decide what to observe, subject to a constraint on information flow. When idiosyncratic conditions are more variable or more important than aggregate conditions, firms pay more attention to idiosyncratic conditions than to aggregate conditions. When we calibrate the model to match the large average absolute size of price changes observed in the data, prices react fast and by large amounts to idiosyncratic shocks, but prices react only slowly and by small amounts to nominal shocks. Nominal shocks have persistent real effects. We use the model to investigate how the optimal allocation of attention and the dynamics of prices depend on the firms' environment.Key words and phrases: rational inattention ; sticky prices ; real effects of nominal shocks
Keywords: E3; E5; D8; 330; Betriebliche Preispolitik; Entscheidung bei Unsicherheit; Unvollkommene Information; Wirtschaftsmodell